Magnetic-field and confinement effects on the effective Land, g factor in AlxGa1-xAs parabolic quantum wells - Bruno-Alfonso, A. [UNESP]; Lopez, F. E.; Raigoza, N.; Reyes-Gomez, E. (Springer, 2010)
The magnetic-field and confinement effects on the Land, factor in AlxGa1-xAs parabolic quantum wells under magnetic fields applied parallel or perpendicular to the growth direction are theoretically studied. Calculations are performed in the limit of low temperatures and low electron density in the heterostructure. The g factor is obtained by taking into account the effects of non-parabolicity and anisotropy of the conduction band through the 2 x 2 Ogg-McCombe Hamiltonian, and by including the cubic Dresselhaus spin-orbit term. A simple formula describing the magnetic-field dependence of the effective Land, factor is analytically derived by using the Rayleigh-Schrodinger perturbation theory, and it is found in good agreement with previous experimental studies devoted to understand the behavior of the g factor, as a function of an applied magnetic field, in semiconductor heterostructures. Present numerical results for the effective Land, factor are shown as functions of the quantum-well parameters and magnetic-field strength, and compared with available experimental measurements.